Prevalensi Maloklusi Anterior pada Anak Usia 8-12 tahun di SDN Renged 1 Tangerang - Firdaus, Moch G.; Siregar, Fazwishni (e-GiGi, 2025)
Abstract: Epidemiologic data on the prevalence of malocclusion is an important determinant in planning appropriate orthodontic services. This study aimed to describe the prevalence of anterior dental malocclusion which were crowding, spacing, protrusion teeth, crossbite, deep bite, and openbite among children. The study involved 106 students aged 8-12 years at Sekolah Dasar Negeri Renged I Tangerang (Elementary School) taken by stratified random sampling technique. Crowding teeth was measured by malalignment score using 45o ended plastic ruler, while crossbite and openbite were examined by inspection. The results showed that only 6.6% had normal occlusion and 93.4% had anterior dental malocclusion. Most cases were crowding (25.65%), followed by spacing, protrusion teeth, deep bite, anterior open bite, and anterior cross bites of 151 total cases. Statistical test showed significant relationships between age and crowding, spacing teeth, and cross bites. Meanwhile, there were no relationships between age and protrusion teeth, deep bite, and open bite. There was no significant relationship between gender and all types of anterior malocclusions. In conclusion, there is a high prevalence of anterior malocclusion among 8-12 years old children in Elementary School Renged I Tangerang. Keywords: anterior malocclusion prevalence; children aged 8-12 years Abstrak: Data epidemiologi mengenai prevalensi maloklusi anterior merupakan faktor penting dalam perencanaan yang tepat untuk layanan ortodontik. Penelitian ini bertujuan untuk mengetahui prevalensi berbagai kasus maloklusi anterior meliputi gigi berjejal, bercelah, gigi protrusif, gigitan silang, gigitan dalam dan terbuka pada anak. Subyek penelitian melibatkan 106 anak sekolah usia 8-12 tahun di Sekolah Dasar Negeri Renged I Tangerang. Pengukuran gigi berjejal dilakukan dengan skor indeks malalignment menggunakan penggaris plastik berujung 45o, sedangkan pengukuran gigi bercelah dilakukan dengan jangka berujung runcing, serta gigitan silang dan gigitan terbuka dilihat dengan inspeksi. Hasil pemeriksaan menunjukkan hanya 6,6% anak memiliki oklusi normal dan 93,4% mengalami maloklusi anterior. Jenis kasus maloklusi anterior terbanyak berturut-turut ialah gigi berjejal (25,65%), gigi bercelah, gigi protrusif, deep bite, open bite, dan cross bite dari total 151 kasus. Uji statistik menunjukkan adanya hubungan bermakna antara kelompok usia dengan gigi berjejal, gigi bercelah, dan gigitan silang namun tidak terdapat hubungan bermakna dengan gigi protrusif, gigitan dalam, serta gigitan terbuka. Tidak terdapat hubungan bermakna antara jenis kelamin dengan seluruh jenis kasus maloklusi. Simpulan penelitian ini ialah terdapat prevalensi maloklusi anterior yang tinggi pada anak usia 8-12 tahun di SDN Renged I Tangerang. Kata kunci: prevalensi maloklusi anterior; anak usia 8-12 tahun